Application and Development of Colloidal Gold Labeling Technique - Wang, Jingyao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The colloidal gold labeling technique has gained widespread popularity in biomedical research due to its versatility and effectiveness. This technology, which has evolved from the use of fluorescence, radioisotopes, enzymes, and other markers, has emerged as a novel biosensor technology with extensive applications. In recent years, colloidal gold antibody labeling technology has been widely utilized in various fields, including biomedicine, food safety, and environmental protection. Its ability to accurately detect and quantify specific molecules makes it an invaluable tool for researchers. This paper aims to provide a comprehensive review of the development history, technical principles, applications, and advantages of colloidal gold antibody labeling technology. By thoroughly understanding these aspects, researchers can gain insights into how this technology can be further developed and improved for future applications. Moreover, the continued advancement of colloidal gold antibody labeling technology holds great promise for enhancing the early diagnosis of diseases and improving the monitoring of environmental contaminants.